Solvent free one-pot multi-component synthesis of beta-azaarene substituted ketones via a Sn-catalyzed C(sp(3))-H functionalization of 2-alkylazaarenes - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Mulla, Shafeek A. R. (RSC Advances, 2015)
A tin-catalyzed solvent free one-pot multi-component cascade reaction strategy for the direct Michael addition/C(sp(3))-H functionalization of 2-alkylazaarenes with aldehydes and ketones via an aldol reaction has been developed. This is the first report and provides cost effective new access to potent biologically/medicinally important azaarene derivatives with high atom economy.

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles

Base‐promoted heterogeneous reusable copper fluorapatite (CuFAP) catalyzed facile synthesis of 1,2‐diarylethanols via C(sp3)‐H functionalization of nitrotoluene - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R. (Chemistryselect, 2018)
A novel, an efficient protocol has been developed for the facile synthesis of various 1,2‐diarylethanol in good to excellent yields via C(sp3)‐H functionalization of various nitrotoluenes with substituted aromatic, heterocyclic aldehydes/isatin. This is the first example in which base promoted heterogeneous, reusable copper fluorapatite (CuFAP) catalyzed C(sp3)‐H functionalization of various nitrotoluenes was achieved under ligand‐, additive‐ free reaction condition. The developed protocol is an environmentally benign approach, which replaces cumbersome protocols, avoids the use of costly precious metal catalysts, prefunctionalized substrates, and toxic reagents. The heterogeneous CuFAP catalyst was recovered by simple filtration and reused several times without the loss of its catalytic activity. The selective functional group transformation of 1,2‐diaryethanol was accomplished.

One-pot cascade synthesis of 2-cyanoacrylamides via Sn-catalyzed acetic acid free selective monohydration of dinitrile - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R. (ChemistrySelect, 2018)
The simple, mild, novel and an efficient new protocol has been developed for the straightforward synthesis of 2-cyanoacrylamides. This is the first report in which Sn-catalyzed acetic acid free selective monohydration of dinitrile was achieved for a one pot cascade synthesis of 2-cyanoacrylamides in good to excellent yield via condensation of various aldehydes, heterocyclic aldehydes with malononitrile.
Keywords: 2-cyanoacrylamides; Aldehyde; one pot; SnCl2 center dot 2H(2)O